Compactness measurement using fuzzy multicriteria decision making for redistricting - Wang, Yin Chai; Bong, Chin Wei (IEEE, 2002)
This paper presents a new method for compactness assessment in redistricting planning using Fuzzy Multicriteria Decision Making. An Enhanced Compactness Index (ECI) representing the overall plan with respect to each criterion is obtained by using triangular fuzzy number. The ECI is generated based on the synthesis of the concepts of fuzzy set theory, AHP, /spl alpha/-cuts concept and index of optimism of district planners to estimate the degree of satisfaction of the judgements on a district plan. The proposed method is more flexible, simple and comprehensive with easy computation and efficiency which facilitates its uses In compactness measurement in redistricting application like school redistricting, election boundary redistricting and others. A case study on forest blocking Is presented to demonstrate Its applicability in redistricting applications with respect to their redistricting goals and criteria.